Innovation, transformation, and war : counterinsurgency operations in Anbar and Ninewa Provinces, Iraq, 2005-2007. - Russell, James A. (James Avery), 1958- (Stanford University Press, 2010)
Within a year of President George W. Bush announcing the end of major combat operations in Iraq in May 2003, dozens of attacks by insurgents had claimed hundreds of civilian and military lives. Through 2004 and 2005, accounts from returning veterans presaged an unfolding strategic debacle--potentially made worse by U.S. tactics being focused on extending conventionally oriented military operations rather than on adapting to the insurgency. By 2007, however, a sea change had taken place, and some U.S. units were integrating counterinsurgency tactics and full-spectrum operations to great effect.